Recrystallization in the metal of welding joints of steam trucks - Dmytryk, V.V.; Glushko, A.V.; Tsar, A.K. (Вопросы атомной науки и техники, 2019)
The recrystallization process in the structure of welded joints of steam pipelines from heat-resistant pearlitic steels, operated for a long time under creep conditions (Te = 545…585 °С, Рe = 20…25 MPa), reduces their performance. Studying the peculiarities of the recrystallization process will allow slowing down its passage, which is important for increasing the service life of welded joints of steam pipelines, which are characterized by the presence of a certain structural heterogeneity.